2020
DOI: 10.1002/aic.16969
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of sands and Geldart A biomass co‐fluidization

Abstract: This article investigated the fluidization of sands and small Geldart A biomass mixtures. The mixture fluidized like Geldart A type particles with a uniform bed expansion regime before bubbling. The video recorded color distance between pure sands and sands-biomass mixtures was used to estimate the sands-biomass mixing. The coarse-grained computational fluid dynamics-discrete element method with a hybrid drag model which couples the Syamlal-O'Brien drag and a filtered drag can capture the mixing while the simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…The third drag model used in this research was derived for coarse grid simulation of small Geldart A particles by filtering fine grid simulation results 43 . It has been used to simulate the co‐fluidization of sands and Geldart A biomass particles 44 . Its formation is attached in Appendix B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third drag model used in this research was derived for coarse grid simulation of small Geldart A particles by filtering fine grid simulation results 43 . It has been used to simulate the co‐fluidization of sands and Geldart A biomass particles 44 . Its formation is attached in Appendix B.…”
Section: Methodsmentioning
confidence: 99%
“…43 It has been used to simulate the co-fluidization of sands and Geldart A biomass particles. 44 Its formation is attached in Appendix B.…”
Section: Drag Modelsmentioning
confidence: 99%
“…The fast pyrolysis of biomass was investigated using a multiscale approach, combining coarse-grain particle scale simulations with reactor scale modelling [91,92]; similarly, coarse grain DEM-CFD combined with reduced-order modelling was used to simulate a pilot-scale updraft coal gasification reactor [93]. Bubbling fluidization of a sand-biomass mixture was compared against experiment for degree of mixing and pressure drop (average and fluctuations) [94,95]. Different testing methods for measuring solids distribution have been compared and improved by simulating the so-called "travelling fluidized bed" [96].…”
Section: Bubbling/spouted/liquid Fluidized Bedsmentioning
confidence: 99%
“…Further investigation 19 showed that the Ganser correction 21 of the Gidaspow drag model 22 can be used to calculate the drag coefficient of non‐spherical biomass particles as it accounts for the influence of particle shapes. For coarse grid CFD simulations of Geldart‐A particles (biochar in this research), the unresolved sub‐grid structures can be accounted with the filtered drag model 23,24 that is a correction to the regular drag models such as the Wen‐Yu drag model. In this article, the filtered drag is coupled with the Ganser drag to address the influence of both unresolved sub‐grid structures and particle shapes. βGanserFilteredgoodbreak=βGanserWenYu()1goodbreak−HFiltered where βGanserFiltered is the drag coefficient combines sub‐grid correction and non‐spherical correction.…”
Section: Computational Fluid Dynamic Modelsmentioning
confidence: 99%